Prognostic score predicting overall survival of patients with intermediate stage of hepatocellular carcinoma after transcatheter transarterial chemoembolization - S. Jarupongprapa (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF Thailand 2019 Background: Except benefits, patients with intermediated stage of hepatocellular carcinoma undergoing Transcatheter arterial chemoembolisation (TACE) might be dealt with TACE-related adverse events, especially liver decompensation. The aim of this study is to develop a prognostic score for avoiding unnecessary retreatment with TACE. Materials and Methods: A retrospective cohort study between January 2007 and December 2012 at Siriraj Hospital, Mahidol University including 216 patients with intermediate stage of HCC undergoing consecutive TACE within 90 days. We investigated the effect of baseline characteristics, liver function, and dynamic tumor response after TACE session on the median overall survival. Results: Five independent parameters impacted on overall survival (OS) with statistical significance in multivariate analysis. These factors were baseline Child-Pugh score (CTP) class B (hazard ratio [HR] 1.77, p = 0.04), the Barcelona Clinic Liver Cancer (BCLC) stage B (HR 1.95, p = 0.001), increased CTP score (+1 [HR 2.29], +2 [HR 11.74], p<0.001], baseline AFP level >200 and <50% reduction after TACE (HR 2.07, p = 0.003) as well as radiologic response (HR 1.56, p = 0.01). The new prognostic score was developed and divided into 2 groups (<3 point and >3 point) with different prognosis (median OS 26.3 months vs. 10.7 months, p<0.001). Furthermore, prognostic score of >3 point was associated with higher TACE related liver decompensation with relative risk 20.2 (p<0.001). Conclusion: Patients with prognostic score >3 point prior second TACE had poor prognosis and high rate of major complication. Retreatment with TACE should be avoided.